Analysis of Infrastructure Governance-Based Contractor Performance Supervision in Road Maintenance Projects in West Limboto District - Dwi Sarmila Zees; Rifka S. Akibu; Widya Kurniati Mohi; Sakbir (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Monitoring contractor performance is an important part of ensuring the quality of work in accordance with technical standards and community interests. This study aims to analyze the performance supervision of contractors based on Infrastructure Governance in road maintenance projects in West Limboto District. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study show that Infrastructure Governance-based contractor performance supervision has been implemented, but it is not optimal. From the aspect of transparency, information on planning, implementation, and progress of road maintenance has not been conveyed evenly to the community, even though it has been carried out through the installation of project boards, socialization, and direct communication in the field. From the aspect of accountability, it is not optimal because the conformity between technical standards and work results is not fully guaranteed, as shown by the discovery of roads that are quickly damaged, even though supervision is carried out through administrative inspections and field monitoring. From the aspect of integrity, the quality of work at some points is still not optimal due to external factors, even though material testing, SOP implementation and supervision have been carried out. From the aspect of responsibility, the implementation of supervision is still constrained due to budget limitations and the number of road sections that must be handled, even though the handling of damage reports, checks and repairs during the maintenance period has been carried out. From the aspect of participation, it is not optimal because community involvement is still limited in planning and evaluation, although there have been complaints and reports related to road conditions. Thus, the supervision of contractor performance needs to be strengthened to ensure the quality of sustainable road infrastructure and increase public confidence in the performance of local governments.